2022
DOI: 10.3390/md20040228
|View full text |Cite
|
Sign up to set email alerts
|

Salmon Protein Hydrolysate Potentiates the Growth Inhibitory Effect of Bicalutamide on Human Prostate Cancer Cell Lines LNCaP and PC3 by Modulating Iron Homeostasis

Abstract: Prostate cancer is a common cause of cancer death in men. In advanced stages of prostate cancer, androgen deprivation therapy (ADT) is initiated. Despite ADT, prostate cancers invariably progress to become androgen independent. A growing body of evidence implicates iron dysmetabolism in prostate cancer progression. A bioactive peptide-rich salmon protein hydrolysate (SPH) has previously been demonstrated to modulate iron homeostatic mechanisms. In the present study, the anticancer effect of SPH and bicalutamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…Lastly, after incubation with FT-005-E, the colony survival rate of VCaP cell colonies decreased to 23%. We may summarize this by stating that a general agreement appears to exist between the data and results presented herein and those reported in our previous in vitro study employing an SPH and bicalutamide treatment protocol in PCa cells [47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lastly, after incubation with FT-005-E, the colony survival rate of VCaP cell colonies decreased to 23%. We may summarize this by stating that a general agreement appears to exist between the data and results presented herein and those reported in our previous in vitro study employing an SPH and bicalutamide treatment protocol in PCa cells [47].…”
Section: Discussionsupporting
confidence: 90%
“…Previous preliminary studies by the authors revealed that a soluble protein hydrolysate (SPH) was capable of significantly altering the expression of ferritin heavy chain 1 (FTH1) and transferrin receptor (TFRC) expression in gingival epithelial cells [46]. In a followup study, this SPH was shown to significantly enhance the efficacy of a first-generation antiandrogen in two types of PCa cells [47]. The extent to which gene modulation was altered corresponded to the magnitude of the effect on suppressing growth of PCa cells in the same study.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Bjerknes et al showed that co-treatment of 160 µg/mL SPH with 1.0 µM bicalutamide decreased the relative colony survival of LNCaP cells from 25% to 2% after culturing for 12 days. The inhibitory effects were related to significant ferritin heavy chain 1 (FTH1) up-regulation [ 111 ].…”
Section: Marine Macroorganismsmentioning
confidence: 99%
“…Bjerknes and colleagues characterized a salmon protein hydrolysate and showed its synergistic effect in combination with bicalutamide in human prostate cancer cells. The mechanism of this phenomenon was described as the modulation of iron homeostasis [22]. The group of von Amsberg investigated the cytotoxic anticancer activity of N-methylpretrichodermamide B in drug-resistant prostate cancer cells in vitro.…”
mentioning
confidence: 99%